Perubahan Morfologi Beberapa Varietas Padi Melalui Pemberian Pemupukan Nitrogen di Lahan Pasang Surut - Gribaldi Gribaldi; Nurlaili Nurlaili (Seminar Nasional Lahan Suboptimal, 2019)
Gribaldi G, Nurlaili N. 2019.  Morphological changes in some rice varieties through giving nitrogen fertilization in tidal land. In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal 2019, Palembang 4-5 September 2019. pp. 353-359.  Palembang: Unsri Press. The increasing of rice production on suboptimal lands especially tidal land every year continues to be improved, one of which is through the use of alternative varieties and the provision of sufficient inputs. This study aims to determine the morphological changes of several rice varieties through the provision of N fertilizer in Tidal Land. The experimental design used in this study was a split plot design with three replications. Main plot: Application of nitrogen (N) fertilizer, namely N1= fertilizing at a dose of 90 kg N/ha; N2= fertilizing with a dose of 135 kg N/ha. Subplot: rice variety (V), V1= Inpari 30, V2 = Inpari 3, V3= Inpari 33, V4= Inpari 43, and V5= Hipa 5 Cepa. The result showed that varieties and N fertilization had an effect on the growth of several rice varieties, at the age of 42 HST in tidal land, the Hipa 5 Cepa variety tended to have better growth, at the age of 42 HST in tidal land, and treatment with doses of nitrogen fertilizer 90 kg/ha produces the best growth in some rice varieties, age 42 HST in tidal land.Keywords:  N fertilization, rice varieties, tidal land